2017
DOI: 10.4172/2161-0932.1000447
|View full text |Cite
|
Sign up to set email alerts
|

Use of Magnesium Sulphate in the Management of Severe Preeclampsia at the Centre University Hospital of Mother and Child (CHU-MEL) Cotonou Benin

Abstract: Objectives: To evaluate professionals practices and the contribution of magnesium sulphate in a better medical care for persons with severe preeclampsia at CHU-MEL. Materials and Method:We conducted a retrospective and cross-sectional study with the aim come up with a descriptive and analytical paper. Our study was conducted from January 15th, 2015 to July 15th, 2016, i.e. during eighteen (18) months. The sampling was exhaustive. The population was made of all patients admitted for severe preeclampsia with or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Findings from previous studies showed that the main functional, physical, and biological signs pre‐eclamptic women presented with on admission were headache, systolic blood pressure equal to or greater than 160 mm Hg and diastolic blood pressure equal to or greater than 110 mm Hg, and hyperuricemia . This was substantiated with the findings in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from previous studies showed that the main functional, physical, and biological signs pre‐eclamptic women presented with on admission were headache, systolic blood pressure equal to or greater than 160 mm Hg and diastolic blood pressure equal to or greater than 110 mm Hg, and hyperuricemia . This was substantiated with the findings in the present study.…”
Section: Discussionmentioning
confidence: 99%